2021
DOI: 10.1002/acr.24186
|View full text |Cite
|
Sign up to set email alerts
|

Are Health Care Professionals’ Implicit and Explicit Attitudes Toward Conventional Disease‐Modifying Antirheumatic Drugs Associated With Those of Their Patients?

Abstract: Objective It is generally unknown how the attitudes and beliefs of health care professionals (HCPs) might affect the attitudes, beliefs, and medication‐taking behavior of patients with rheumatoid arthritis (RA). This study aims 1) to examine the attitudes, health‐related associations (both implicit and explicit), and beliefs of HCPs about conventional disease‐modifying antirheumatic drugs, and 2) to assess whether these attitudes, health‐related associations, and beliefs of HCPs are associated with those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…We found no associations between physicians’ medication beliefs and their prescribed dosage of allopurinol, gout outcomes or the medication beliefs of patients. This is in line with earlier research in rheumatology [ 19 ]. Of note, in our unadjusted model, a higher concern score was associated with a lower prescribed dosage of allopurinol.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found no associations between physicians’ medication beliefs and their prescribed dosage of allopurinol, gout outcomes or the medication beliefs of patients. This is in line with earlier research in rheumatology [ 19 ]. Of note, in our unadjusted model, a higher concern score was associated with a lower prescribed dosage of allopurinol.…”
Section: Discussionsupporting
confidence: 93%
“…In line with other studies, we found that physicians reported a greater need and fewer concerns for their prescribed medication [ 19–21 ]. The average necessity score falls in the range of previous studies regarding beliefs regarding statins and DMARDs (13.9–20.9) [ 19–21 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations